Thermo- and Light-Responsive Polymer-Coated Magnetic Nanoparticles as Potential Drug Carriers - Cui, Guihua; Wang, Hao; Long, Shengsen; Zhang, Tianshuo; Guo, Xiaoyu; Chen, Shuiying; Kakuchi, Toyoji; Duan, Qian; Zhao, Donghai (Frontiers in Bioengineering and Biotechnology, 2022)
A series of thermo- and light-responsive copolymers of poly(N-isopropylacrylamide) (PNIPAM) and 6-[4-(4-methoxy phenyl azo)-phenoxyl-hexyl methacrylate)(AzoMA) (PNIPAM-b-PAzoMA) were synthesized via Reversible Addition-Fragmentation Chain Transfer (RAFT) radical polymerization. The resulting copolymers had a narrow molecular weight distribution range of 1.06~1.24, which Mn changed regularly with monomer concentration. Subsequently, the diblock copolymers were successfully modified on the surface of iron oxide nanoparticles through the interaction between the chemical bonds to prepare Fe3O4@(PNIPAM-b-PAzoMA). The sizes of fabricated nanoparticles with excellent thermo-sensitivity and photo-sensitivity were controlled at about 40 to 50 nm. Cell viability assays suggested that these nanoparticles showed excellent biocompatibility and potential drug delivery in tumor microenvironment.